Epoxy resin hybrid insulating material with lasting low-temperature toughness and high hydrophobicity and preparation method of epoxy resin hybrid insulating material

By introducing silicone epoxy monomer and polysiloxane modifications into the insulating material of high-voltage transmission line, adding composite fillers and fluorination treatment, the problems of insufficient mechanical toughness and interface incompatibility of the material in low-temperature environments are solved, and efficient improvement of low-temperature toughness and hydrophobic performance are achieved.

CN119613922AInactive Publication Date: 2025-03-14TIANFU YONGXING LAB
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411950517.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing high-voltage transmission line insulation materials are insufficient in low temperature environments, interface incompatibility leads to limited hydrophobicity, and the addition of fillers may sacrifice the overall structural mechanical properties.

Method used

By introducing silicone epoxy monomers and polysiloxane modifications into the epoxy resin, the chemical network structure and interface compatibility are improved, and composite fillers are added and fluorinated to improve the low-temperature toughness and hydrophobic properties of the material.

Benefits of technology

It achieves the improvement of mechanical toughness and lasting hydrophobic properties in low temperature environments, improves the overall structural mechanical properties and interface compatibility of the material, and reduces the negative impact of filler addition on the mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214760210000091
    Figure BDA0005214760210000091
Patent Text Reader

Abstract

The invention relates to the technical field of electrical insulating materials for power transmission lines, and discloses a low-temperature-toughness durable high-hydrophobicity epoxy resin hybrid insulating material and a preparation method thereof. Comprising 50-100 parts of an epoxy monomer, 5-50 parts of a siloxane-based epoxy monomer, 30-80 parts of a curing agent, 8-20 parts of a polysiloxane modifier, 10-30 parts of a composite filler, 1-10 parts of an acid-base accelerator, 80-160 parts of aluminum hydroxide, 80-120 parts of silicon powder and 5-25 parts of a silane coupling agent. A chemical network structure on a molecular level is designed, a siloxane epoxy monomer with excellent low-temperature mechanical toughness and high hydrophobicity is introduced, a polysiloxane chain segment is subjected to modification treatment and chemically crosslinked with a functional group of a curing agent, the problem of interfacial compatibility is solved, a composite filler capable of improving compatibility is added, and the curing agent is prepared. According to a free radical reaction mechanism, the surface of the formed insulating material is subjected to rapid fluorination treatment, and the epoxy resin-based hybrid insulating material is endowed with mechanical toughness and lasting hydrophobic performance in a low-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrical insulation materials for power transmission lines, and in particular to a low-temperature toughness, durable, highly hydrophobic epoxy resin hybrid insulation material and a preparation method thereof. Background Art

[0002] The insulation materials of high-voltage transmission lines are crucial components in the power system, among which insulators are the most widely used. They are the key to ensure electrical insulation between high-voltage wires and other structures such as towers and poles, and need to withstand the mechanical load of the line. Currently, there are three main types of insulators for high-voltage transmission lines: ceramic insulators, glass insulators, and silicone rubber hybrid insulators.

[0003] Under the same conditions, ceramic insulators have good mechanical properties and can withstand certain mechanical loads. At the same time, the inherent high insulation properties of ceramic materials give ceramic insulators excellent insulation properties. However, ceramic insulators are also brittle and have relatively low impact resistance. They are prone to breakage when subjected to excessive force, and lead to zero-value breakdown, causing serious economic losses and safety accidents. Glass insulators are not easy to accumulate dirt and are easy to clean. After years of operation, their electromechanical properties are basically the same as when they left the factory, and no aging phenomenon occurs. However, they have their own self-explosion characteristics. When encountering internal defects or external impacts, they are easy to break by themselves, causing major safety accidents. The above two insulating materials are both hydrophilic materials with poor water repellency, which leads to short circuit or leakage of the electrical part of the connector, increasing the safety risks of industrial connectors and supported equipment, and may even cause fires and other accidents that endanger life and property.

[0004] Silicone rubber composite insulators are lightweight, hydrophobic, easy to install, and highly resistant to pollution flashover. In recent years, they have gradually become the mainstream choice for high-voltage transmission lines and are increasingly widely used. However, silicone rubber materials inherently have low strength, poor light and heat aging resistance, and incompatibility between silicone rubber and FRP core rods, which limits their large-scale application.

[0005] In recent years, the development of organic hybrid insulating materials with high strength and excellent hydrophobicity based on different epoxy organic polymers has gradually gained attention and is used to replace traditional insulating materials. This process involves using a variety of aliphatic and aromatic epoxy monomers as a matrix, and adding curing agents with different functional groups and functionalities to manufacture insulating materials with different structural strengths. After ensuring the mechanical strength of the material, organic and inorganic micro-nanoparticles with hydrophobic properties can be introduced by physical blending and combined with organic materials to further enhance their hydrophobic properties, thereby preparing organic hybrid insulating materials with both structural strength and hydrophobic properties.

[0006] At present, it is difficult to achieve the structural and functional integration of insulating materials by only using a single epoxy monomer, screening curing agents, adding functional fillers, and optimizing the preparation process. The main problems include: the addition of fillers may sacrifice the overall structural mechanical properties of the material to a certain extent, the incompatibility of the interface of organic hybrid materials may lead to a decrease in low-temperature toughness, and the addition of single functional particles leads to limitations in hydrophobicity. Summary of the invention

[0007] Technical problems solved by the present invention:

[0008] The addition of fillers to solve the current problems may sacrifice the overall structural mechanical properties of the material to a certain extent, the incompatibility of the interface of organic hybrid materials may lead to a decrease in low-temperature toughness, and the addition of single functional particles leads to limitations in hydrophobicity.

[0009] The technical solution adopted by the present invention is:

[0010] The present application provides a low-temperature toughness, durable, highly hydrophobic epoxy resin hybrid insulating material and a preparation method thereof, which introduces a siloxane epoxy monomer with excellent low-temperature mechanical toughness and high hydrophobicity by designing the chemical network structure at the molecular level, and modifies the polysiloxane chain segment, chemically crosslinks with the functional group of the curing agent to solve the problem of interface compatibility, and adds a composite filler that can improve compatibility. Subsequently, according to the free radical reaction mechanism, the surface of the molded insulating material is subjected to rapid fluorination treatment. This strategy can effectively give the epoxy resin-based hybrid insulating material mechanical toughness and durable hydrophobicity in a low-temperature environment.

[0011] To expand on this, that is to say:

[0012] First, the present invention provides a low-temperature toughness, durable and highly hydrophobic epoxy resin hybrid insulating material. The raw material components, measured by weight, include 50-100 parts of epoxy monomer, 5-50 parts of siloxane-based epoxy monomer, 30-80 parts of curing agent, 8-20 parts of polysiloxane modifier, 10-30 parts of composite filler, 1-10 parts of acid-base accelerator, 80-160 parts of aluminum hydroxide, 80-120 parts of silicon powder, and 5-25 parts of silane coupling agent.

[0013] According to some preferred embodiments, the raw material components, measured by weight, include 65-90 parts of epoxy monomer, 5-45 parts of siloxane epoxy monomer, 35-70 parts of curing agent, 10-18 parts of polysiloxane modifier, 15-25 parts of composite filler, 1-8 parts of acid-base accelerator, 90-150 parts of aluminum hydroxide, 90-115 parts of silicon powder, and 7-20 parts of silane coupling agent.

[0014] According to some preferred embodiments, the epoxy monomer includes at least one of 3,4-epoxycyclohexylmethyl, 3,4-epoxycyclohexylcarboxylate, bis((3,4-epoxycyclohexyl)methyl)adipate, tetrahydroindene diepoxide, 3,4-epoxycyclohexyl methacrylate, 3,4-epoxycyclohexylmethyl methacrylate, 3,4-epoxycyclohexyl methacrylate and vinylcyclohexene dioxide.

[0015] According to some preferred embodiments, the siloxy epoxy monomer includes at least one of 2,4,6,8-tetramethyl-2-[3-(oxiranylmethoxy)propyl]cyclotetrasiloxane, mono(2,3-epoxy)propyl ether-terminated polydimethylsiloxane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 1,3-bis[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]-1,1,3,3-tetramethyldisiloxane, and 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane.

[0016] According to some preferred embodiments, the curing agent includes at least one of methylhexahydrophthalic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, and methyltetrahydrophthalic anhydride.

[0017] According to some preferred embodiments, the acid-base accelerator includes at least one of N,N-dimethylbenzylamine, triethylamine, dimethylaminophenol, dibutyltin diosilicate, and boron trifluoride.

[0018] According to some preferred embodiments, the modified polysiloxane is obtained by reacting APTES with polydimethylsiloxane. Specifically, APTES, 2,3-glycidoxypropyl-terminated polydimethylsiloxane, and toluene are reacted at 110° C. for 8 hours under a nitrogen atmosphere, and then the toluene is removed by rotary evaporation to obtain the modified polysiloxane. The mass ratio of APTES, 2,3-glycidoxypropyl-terminated polydimethylsiloxane, and toluene is 10-15:100:100-120.

[0019] According to some preferred embodiments, the preparation method of the composite filler is that the carbon nanotubes are treated with concentrated acid at 60°C for 10 hours, the concentrated acid is a mixed acid solution with a volume ratio of concentrated sulfuric acid to concentrated nitric acid of 3:1, and the carboxylated carbon nanotubes are obtained after washing and drying. BN is placed in a pH 8.5, 10mM Tris buffer, and then ethanol and dopamine hydrochloride are added and ultrasonically treated for 15 to 30 minutes and 6 to 10 hours, and then washed and dried to obtain amination BN. The ratio of BN, Tris buffer, ethanol, and dopamine hydrochloride is 10g:200mL:100mL:0.5g. Amination BN is dispersed in a 2mg / mL PEI solution, and after ultrasonic treatment for 30 to 60 minutes, it is washed and dried, and then it and the carboxylated carbon nanotubes are placed in a Tris buffer for ultrasonic treatment for 3 to 6 hours, and the composite filler is obtained after washing and drying. The mass ratio of amination BN, PEI, and carboxylated carbon nanotubes is 1:1.5 to 3:1.

[0020] Second, the present invention provides a method for preparing the aforementioned low-temperature toughness, durable, highly hydrophobic epoxy resin hybrid insulating material, comprising the following steps:

[0021] (1) Aluminum hydroxide, silicon powder, and silane coupling agent KH550 are stirred and blended in acetone at 50 to 70° C. for 2 to 4 hours to obtain a first blend;

[0022] (2) blending the epoxy monomer, the siloxane-based epoxy monomer, the polysiloxane modified substance, and the composite filler at 40 to 60° C. for 0.5 to 1.5 hours to obtain a second blend;

[0023] (3) blending the second blend, the curing agent, and the acid-base accelerator at 40-60° C. for 2-4 hours to obtain a third blend;

[0024] (4) blending the third blend and the first blend at 40 to 60° C. for 1 to 3 hours to obtain a prepreg;

[0025] (5) placing the prepreg in an oven, setting the vacuum degree to 0.1-1 MPa, and maintaining the vacuum degree for 6-12 hours; and then, performing injection molding and curing to obtain an insulator;

[0026] (6) Place the insulator in a closed reactor, remove the internal air, and introduce F into the reactor. 2 / N 2 Mixed gas, F 2 The volume concentration is 1-20%, and the fluorination treatment is performed at room temperature to 150°C, 0 to 60 minutes, and 0 to 100 KPa. After the fluorination treatment, the insulating material is obtained.

[0027] The technical mechanism and beneficial effects adopted by the present invention are as follows:

[0028] (1) By adding siloxane-based epoxy monomers, the chemical network structure of the epoxy resin base is changed to achieve low-temperature toughness and hydrophobic properties, and the interface problem of physical doping is weakened through the chemical structure.

[0029] (2) By adding polysiloxane modifiers and introducing flexible polysiloxane segments, it forms an interwoven network structure with the epoxy resin, thereby improving the compatibility of the two, while also enhancing low-temperature toughness, hydrophobicity, and heat resistance.

[0030] (3) By adding composite fillers, the problem of decreased mechanical properties caused by improving epoxy resin by siloxane can be improved. However, adding fillers will also cause problems of interface defects and poor interface bonding. Based on this, PEI is used as an intermediate. Its active groups can not only provide active sites for the filler, but also have good compatibility with epoxy resin, which can simultaneously improve the toughness and impact strength of epoxy resin. Carbon nanotube fibers and BN are selected as fillers. Carbon nanotube fibers can more easily form a through filler network in the resin matrix, thereby alleviating the degree of electric field distortion. The addition of BN can improve the insulation performance of the matrix. PEI is then used as a medium, and its own active groups are used to graft carbon nanotubes and BN, thereby avoiding the problem of agglomeration. The compatibility of PEI is used to improve the interfacial bonding performance of the composite material.

[0031] (4) By introducing fluorination treatment, the hydrophobicity of the insulating material can be improved, and at the same time, it can also help improve the UV resistance and aging resistance. Due to its high electronegativity, the fluorine element can improve the electrical insulation properties of the composite material by generating fluorinated groups with deeper trap energy levels in the polymer. Fluorination treatment can also improve the surface conductivity and surface charge decay rate of the insulating material, thereby enhancing its arc resistance.

[0032] (5) The preparation process provided by the present technology jointly determines the homogeneity of the hybrid insulating material through the pretreatment of the material, the pretreatment of the prepreg, and the setting of the curing process parameters. First, improper pretreatment of the material may lead to the formation of micro-nano-scale air holes, which may cause stress concentration during the service of the material, thereby damaging the mechanical properties of the material. Secondly, insufficient pretreatment of the prepreg may lead to incomplete curing of the insulating material and the generation of micro-nano-scale air holes, which will also have an adverse effect on the mechanical properties of the material. Finally, improper adjustment of the curing process parameters may lead to incomplete cross-linking of the material or local gelation, thereby reducing the mechanical properties of the material. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0034] Example 1

[0035] A method for preparing a low-temperature toughness, durable, highly hydrophobic epoxy resin hybrid insulating material comprises the following steps:

[0036] (1) 12 g of APTES, 100 g of 2,3-glycidoxypropyl-terminated polydimethylsiloxane, and 110 g of toluene were placed in a sealed reactor and reacted under a nitrogen atmosphere. After reacting at 110° C. for 8 h, the toluene was removed by rotary evaporation to obtain a modified polysiloxane.

[0037] (2) Take the carbon nanotubes and immerse them in a concentrated acid mixture (V H2SO4 :V HNO3 =3:1) was treated at 60°C for 10h, then washed with deionized water and dried to obtain carboxylated carbon nanotubes. 10g BN was placed in 200mL Tris buffer at pH 8.5 and 10mM, and then 100mL ethanol and 0.5g dopamine hydrochloride were added and ultrasonically treated for 20min and 8h, then washed with deionized water and dried to obtain amino BN. 0.5g amino BN was dispersed in 2mg / mL 500mL PEI solution, ultrasonically treated for 45min, washed with deionized water and dried, and then placed with 0.5g carboxylated carbon nanotubes in Tris buffer for 5h, washed with deionized water and dried to obtain a composite filler.

[0038] (3) 8 to 24 hours before preparation, aluminum hydroxide is placed in a blast or vacuum oven at 50 to 70° C. for pretreatment. 100 parts of aluminum hydroxide, 100 parts of silicon powder, and 20 parts of KH550 are stirred and blended in acetone at 60° C. for 3 hours to obtain a first blend.

[0039] (4) The temperature of the stirrer is preset to 30-50° C., and the mixture is kept warm for 1-2 hours. After the heat preservation is completed, materials are added in batches. 80 parts of 3,4-epoxycyclohexylcarboxylate, 40 parts of 2,4,6,8-tetramethyl-2-[3-(oxiranylmethoxy)propyl]cyclotetrasiloxane, 15 parts of modified polysiloxane, and 20 parts of composite filler are mixed at 50° C. for 1 hour with a stirring speed of 100 rpm to obtain a second blend.

[0040] (5) The second blend, 60 parts of phthalic anhydride, and 5 parts of N,N-dimethylbenzylamine were blended at 50° C. for 2 hours to obtain a third blend.

[0041] (6) The third blend and the first blend were blended at 50° C. for 1 h with a stirring speed of 300 rpm / min to obtain a prepreg.

[0042] (7) Load the prepreg into a large mold, and then place it in an oven, set the vacuum degree to 0.8MPa, and maintain it for 10 hours. Before injection molding, remove impurities from the industrial mold, and then place the mold in a large oven set at 50-100℃ for preheating treatment. The preheating time is 1-2 hours. After the mold is preheated, a water-based release agent is used to coat the mold surface. After the coating is completed, the prepreg is slowly injected into the mold. After the injection molding is completed, it is placed in a vacuum oven preheated to 50℃. After placing it, slowly adjust the vacuum degree of the oven several times (5-10 times) to reach a vacuum degree of 0.8~1MPa, and then keep it warm and pressurized for 1~2 hours. After the heat and pressure treatment is completed, adjust the oven temperature to 100℃ and keep it warm for 3 hours. After the heat and pressure treatment is completed, adjust the temperature to 120℃, adjust the vacuum degree of the oven to 1.5~2MPa, and keep it warm and pressurized for 34 hours. After the end, continue to adjust the temperature to 150°C under the same pressure conditions, keep the temperature and pressure for 3 hours, turn off the heating device after the end, let it cool naturally, and obtain the insulator.

[0043] (5) After curing, clean the surface of the insulator with ethanol and then dry it. Place the insulator in a closed reactor, remove the internal air, and control the internal moisture to ppm level. 2 / N 2 Mixed gas, F 2 The volume concentration is 10%, and the fluorination treatment is: 80°C, 45min, 20KPa. After the fluorination treatment, the insulating material is obtained.

[0044] Comparative Example 1

[0045] The difference between Comparative Example 1 and Example 1 is that 3,4-epoxycyclohexylcarboxylate is not added.

[0046] Comparative Example 2

[0047] The difference between this comparative example and Example 1 is that no polysiloxane modification material is added.

[0048] Comparative Example 3

[0049] The difference between this comparative example and Example 1 is that the composite filler is obtained after BN and carbon nanotubes are treated with KH550.

[0050] Comparative Example 4

[0051] The difference between this comparative example and Example 1 is that no fluorination treatment is performed.

[0052] The insulating materials prepared in Example 1 and Comparative Examples 1-3 were used as samples to measure the material performance indicators. The results are shown in Table 1.

[0053] Table 1

[0054]

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A low-temperature toughness, durable, highly hydrophobic epoxy resin hybrid insulating material, characterized in that: The raw material components are calculated by weight and include 50-100 parts of epoxy monomer, 5-50 parts of siloxane-based epoxy monomer, 30-80 parts of curing agent, 8-20 parts of polysiloxane modifier, 10-30 parts of composite filler, 1-10 parts of acid-base accelerator, 80-160 parts of aluminum hydroxide, 80-120 parts of silicon powder, and 5-25 parts of silane coupling agent.

2. The low-temperature toughness durable high hydrophobic epoxy resin hybrid insulating material according to claim 1, characterized in that: The raw material components are calculated by weight and include 65-90 parts of epoxy monomer, 5-45 parts of siloxane epoxy monomer, 35-70 parts of curing agent, 10-18 parts of polysiloxane modifier, 15-25 parts of composite filler, 1-8 parts of acid-base accelerator, 90-150 parts of aluminum hydroxide, 90-115 parts of silicon powder and 7-20 parts of silane coupling agent.

3. The low-temperature toughness durable high hydrophobic epoxy resin hybrid insulating material according to claim 1, characterized in that: The epoxy monomer includes at least one of 3,4-epoxycyclohexylmethyl, 3,4-epoxycyclohexylcarboxylate, bis((3,4-epoxycyclohexyl)methyl)adipate, tetrahydroindene diepoxide, 3,4-epoxycyclohexyl methacrylate, 3,4-epoxycyclohexylmethyl methacrylate, 3,4-epoxycyclohexyl methacrylate and vinylcyclohexene dioxide.

4. The low-temperature toughness durable high hydrophobic epoxy resin hybrid insulation material according to claim 1, characterized in that: The siloxy epoxy monomer includes at least one of 2,4,6,8-tetramethyl-2-[3-(oxiranylmethoxy)propyl]cyclotetrasiloxane, mono(2,3-epoxy)propyl ether terminated polydimethylsiloxane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 1,3-bis[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]-1,1,3,3-tetramethyldisiloxane, and 1,1,3,3-tetramethyl-1,3bis[3-(oxiranylmethoxy)propyl]disiloxane.

5. The low-temperature toughness durable high hydrophobic epoxy resin hybrid insulation material according to claim 1, characterized in that: The curing agent includes at least one of methylhexahydrophthalic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, and methyltetrahydrophthalic anhydride.

6. The low-temperature toughness durable high hydrophobic epoxy resin hybrid insulating material according to claim 1, characterized in that: The acid-base accelerator includes at least one of N,N-dimethylbenzylamine, triethylamine, dimethylaminophenol, dibutyltin diosilicate, and boron trifluoride.

7. The low-temperature toughness, durable and highly hydrophobic epoxy resin hybrid insulating material according to any one of claims 1 to 6, characterized in that: The insulating material comprises at least one of the features (1) to (2): (1) The polysiloxane-modified product is obtained by reacting APTES with polydimethylsiloxane; (2) The composite filler is prepared by ultrasonic treatment of carboxylated carbon nanotubes, PEI and amino BN.

8. The low-temperature toughness durable high hydrophobic epoxy resin hybrid insulating material according to claim 7, characterized in that: The insulating material includes at least one of the features (1-1) to (1-2), (2-1) to (2-3): (1-1) APTES, 2,3-glycidoxypropyl-terminated polydimethylsiloxane, and toluene are reacted at 110° C. for 8 h under a nitrogen atmosphere, and then the toluene is removed by rotary evaporation to obtain a modified polysiloxane; (1-2) the mass ratio of APTES, 2,3-glycidoxypropyl-terminated polydimethylsiloxane, and toluene is 10-15:100:100-120; (2-1) treating carbon nanotubes with concentrated acid at 60°C for 10 hours, wherein the concentrated acid is a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and then washing and drying to obtain carboxylated carbon nanotubes; (2-2) BN is placed in a pH 8.5, 10 mM Tris buffer, and then ethanol and dopamine hydrochloride are added and ultrasonically treated for 15 to 30 min and 6 to 10 h, and then washed and dried to obtain amino BN; (2-3) The mass ratio of amino BN, PEI and carboxylated carbon nanotubes is 1:1.5 to 3:

1.

9. A method for preparing a low-temperature toughness, durable, highly hydrophobic epoxy resin hybrid insulating material as claimed in any one of claims 1 to 8, characterized in that: The steps include: S1: Aluminum hydroxide, silicon powder and silane coupling agent KH550 are stirred and blended in acetone to obtain a first blend; S2: stirring and blending the epoxy monomer, the siloxane-based epoxy monomer, the polysiloxane modified substance, and the composite filler to obtain a second blend; S3: stirring and blending the second blend, the curing agent, and the acid-base accelerator to obtain a third blend; S4: stirring and blending the third blend and the first blend to obtain a prepreg; S5: placing the prepreg in an oven and setting the vacuum degree; Then, the insulator is obtained through injection molding and curing; S6 places the insulator in a closed reactor, removes the internal air, and performs fluorination treatment to obtain an insulating material.

10. The method for preparing the low-temperature toughness durable high hydrophobic epoxy resin hybrid insulating material according to claim 9, characterized in that: Introduce F2 / N2 mixed gas into the reactor, with F2 volume concentration of 1-20%, fluorination treatment: room temperature-150℃, 0-60min, 0-100KPa.

Citation Information

Patent Citations

  • Preparation method and application of chemical-bonded thermally-conductive insulation composite filling material

    CN106380630A

  • Method for promoting dielectric surface flashover strength of epoxy resin

    CN107216483A

  • Small-spacing epoxy molding compound applied to outdoor display screen and preparation method thereof

    CN112852371A

  • Nano-regulation-based multi-scale insulating and heat-conducting PC composite material and preparation method thereof

    CN114196186A

  • Hydrophobic alicyclic epoxy resin insulator material and preparation method thereof

    CN117659625A